ACCOUNTANT'S WARNING REGARDING THE LACK OF MANAGEMENT INTEGRITY - SORIN ADRIAN ACHIM; MARIUS-IONUT SOUCA (Challenges of the Knowledge Society)
This article highlights the challenges faced by accountants when they find that the integrity of company management is poor. The main problem is in relation with the accountants’ fear, mostly: suffering some repercussions from the disclosure of such information. Also, this article aims to emphasize the danger brought by covering and concealing incriminating information against the management; but also, how accountants could expose this information in such a way that they would not suffer, under no circumstances from such disclosures.